2021
DOI: 10.3390/healthcare10010077
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Government Information Supply and Public Information Demand in the Early Stage of COVID-19 in China—An Empirical Analysis

Abstract: Accurate and effective government communication is essential for public health emergencies. To optimize the effectiveness of government crisis communication, this paper puts forward an analytical perspective of supply–demand matching based on the interaction between the government and the public. We investigate the stage characteristics and the topic evolutions of both government information supply and public information demand through combined statistical analysis, text mining, text coding and cluster analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…This is the core of our hypothesis-that the exponential risk of hospitalizations can be used to estimate the burden on hospitals and to provide evidence for exceeded capacity. Once again, it was confirmed that effective government communication is critical for public health crises [17], such as that observed in our country.…”
Section: Discussionsupporting
confidence: 85%
“…This is the core of our hypothesis-that the exponential risk of hospitalizations can be used to estimate the burden on hospitals and to provide evidence for exceeded capacity. Once again, it was confirmed that effective government communication is critical for public health crises [17], such as that observed in our country.…”
Section: Discussionsupporting
confidence: 85%
“…Government efforts to implement public health policies, enhance healthcare delivery, initiate or sponsor epidemiological studies, announce significant scientific breakthroughs, and modify the usual social and economic order comprise another category of health messages [ 27 , 29 , 52 , 53 , 59 , 67 , 68 , 77 , 81 83 ]. The extent to which this information was communicated impacted the effectiveness of these messages.…”
Section: Resultsmentioning
confidence: 99%
“…This aspect was equally significant in understanding public needs in the domain of governance. During the COVID-19 crisis, the research conducted by Zhang and Yu [ 25 ], along with Tang et al [ 26 ], delved into the dynamics between the supply of information by governments and the demands for such information from the public. These studies shed light on both the effectiveness and the challenges inherent in government communication strategies during public health emergencies.…”
Section: Related Workmentioning
confidence: 99%